2017
DOI: 10.7759/cureus.1155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Use of Home Sphygmomanometers Among Hypertensive Patients

Abstract: ObjectiveFew studies have looked at the predictors of use of home sphygmomanometers among hypertensive patients in low-income countries such as Pakistan. Considering the importance of home blood pressure monitoring (HBPM), cross-sectional study was conducted to evaluate the prevalence and predictors of the usage of all kinds of HBPM devices.MethodThis study was conducted in Karachi during the time period of January-February 2017. Adult patients previously diagnosed with hypertension visiting tertiary care hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
(29 reference statements)
1
21
1
1
Order By: Relevance
“…This finding was lower than results reported from a study carried out in Karachi (southern Asia), northeastern Singapore (Asia), northern Carolina, and China where the prevalence of self-Monitoring of BP among hypertensive patients was 25%, 24%, 43.1%, and 24.5% respectively. 35,40,41,44 This variation might be due to the differences in a study setting where a study was conducted at a tertiary hospital for the study in Karachi, and differences in the sample size (700) for the study carried out in northern Carolina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was lower than results reported from a study carried out in Karachi (southern Asia), northeastern Singapore (Asia), northern Carolina, and China where the prevalence of self-Monitoring of BP among hypertensive patients was 25%, 24%, 43.1%, and 24.5% respectively. 35,40,41,44 This variation might be due to the differences in a study setting where a study was conducted at a tertiary hospital for the study in Karachi, and differences in the sample size (700) for the study carried out in northern Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the study conducted in Karachi and Italy. 44,48 This could be due to the fact that higher education provides better information about self-monitoring of BP and hypertension-related complications. The education helps to make the patient conscious of their health status and also creates the opportunity of being aware of the disease condition and its weightiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, health care professionals’ guidance may contribute to more frequent engagement in BP measurement. Studies have indicated the importance of professionals’ guidance on BP measurement [ 26 , 28 ]. Elderly hypertensive patients who had accepted health care professionals’ guidance usually are told to engage in regularly BP measurement.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Para obter um controle da hipertensão arterial sistêmica (HAS), que acomete grande parte da população, é realizada a mensuração das pressões; esse passo é indispensável para o melhor diagnóstico, sendo de maior utilização entre os profissionais o esfigmomanômetro manual. 7 A avaliação da alteração na PA precisa ser feita em aparelhos manuais, visto que estudos comprovam que a aferição automatizada não chega ao nível de precisão de um aparelho manual, tornando o modo manual um padrão de referência para precisão. 8 O presente estudo tem por objetivo descrever, por meio de uma revisão de literatura, a ocorrência de alterações significativas na PA sistêmica de pacientes submetidos a procedimentos cirúrgicos odontológicos.…”
Section: Introductionunclassified